(untitled) (Proceedings of Voronezh State University. Series: Geology, 2019)
The paper provides the description of fragments of the suture zone of the northern frame of DKM. DKM is a Hercynian terrain within the Alpine folded structure of the Western Caucasus. Its geodynamic interpretation is presented. In accordance to this interpretation the Hercynian and Alpine stages of tectonic transformations are distinguished. At the Hercynian stage, at least two continental blocks (terraines) interacted at the collision stage. One of those blocks was preserved in the Alpine structure as a DCM. A fragment of the second is found in the form of a local protrusion at the mouth of the Rufabgocreek. The collisional granitoids had a thermal effect on the serpentinites, turned this rocks into hornfels, and at the same time, under the conditions of compression, they themselves were subjected to a dislocation effect, as a result of which megabreccia with granitoids were formed. In the pre-Upper Jurassic, a reflection of the next compression was the formation of terrigenous melange, the matrix of which were argillites and alevrolites of fore-delta. The suture fragment formed under the conditions of collision and folded with serpentinitemelange, remained a rather mobile zone. In this zone, brittle-plastic deformations were easily realized with the formation of terrigenous melange and the renewal of serpentinitemelange and additional deformations imposed on the Paleozoic megabreccia. The kinematics of dislocations and accompanying events was changing several times during the process of the formation of a mixtite. The most ancient dislocations are associated with upthrust of the DCM on the conjugate Paleozoic block, with the subsequent imposition of the shear component and the bulk flow of the terrigenous melange matrix.